Prevalence of Diabetes and Cardiovascular Comorbidity in the Canadian Community Health Survey 20022003 - Frank Mo; Lisa M. Pogany; Felix C.K. Li; Howard Morrison (The Scientific World Journal)
Diabetes mellitus is a major risk factor for heart disease (heart attack, angina, and heart failure), stroke, and hypertension, which shorten the average life expectancy. The main objective of this study was to describe the prevalence of heart disease, hypertension, and stroke among Canadians with diabetes compared to those without diabetes in the Canadian general population aged 12 years and over. It also estimated the strength of association between diabetes, heart disease, hypertension, and other factors such as age, gender, cigarette smoking, alcohol drinking, education status, body mass index (BMI), and other socioeconomic factors. Descriptive statistics were used initially to estimate the prevalence of related comorbidities by age and gender. Logistic regression was then employed to determine the potential strength of association between various effects. Data included 127,610 individuals who participated in the 2.1 cycles of the Canadian Community Health Survey (CCHS) in 2002—2003. The prevalence of self-reported hypertension, heart disease, and stroke among individuals with diabetes were 51.9, 21.7, and 4.8%, respectively. By comparison, prevalence among those without diabetes was 12.7, 4.2, and 0.9%. Adjusted Odds Ratios (OR) were 4.15, 5.04, and 6.75 for males, and 4.10, 5.29, and 4.56 for females hypertension, heart disease, and stroke, respectively. Lower income (OR from 1.27—1.94) and lower education (OR from 1.23—1.86) were independently associated with a high prevalence of hypertension, heart disease, and stroke among diabetics. Alcohol consumption (OR from 1.06—1.38), high BMI (OR from 1.17—1.40), physical inactivity (OR from 1.21—2.45), ethnicity, and immigration status were also strongly associated with hypertension, heart disease, and stroke. The adjusted prevalence of hypertension, heart disease, and stroke in the CCHS-2003 health survey in Canada was significantly higher among those with diabetes compared to those without. Other factors such as age, gender, BMI, lifestyle, family incomes, physical activity levels, and socioeconomic status also affected the strength of association between diabetes and resulting comorbidities.